Bilateral Blindness Due to Left Fronto-Temporal Lobe Glioblastoma Multiforme - Thapa, Bikram Bahadur; Neupane, Joshan; Moktan, Sunil (Journal of Nepalgunj Medical College, 2020)
Introduction: Glioblastoma multiforme is the most common primary malignant brain tumor, with a very poor prognosis. Direct compression of any structure in the visual pathway or chronic papilloedema is the cause of loss of vision in these patients. Case Report: 30 years old male from Dailekh was brought by his elder brother with the complaint of complete vision loss in both eyes for 45 days. He also had hearing difficulty on right side, headache, right sided weakness and abnormal body movement. His Visual acuity was no perception of Light in both eyes. Pupil was mid-dilated and not reacting to light. Fundus examination revealed bilateral Pallid disc edema. MRI brain revealed left fronto-temporal GBM compressing optic chiasm. Neurosurgical consultation was obtained and counseling was done regarding disease and its treatment. Due to poor prognosis and poverty patient choose palliative conservative treatment. Conclusion: This case highlights the possibility of bilateral Blindness in unilateral GBM. GBM has very poor outcome even after treatment.